An urticarial vasculitis case induced by glatiramer acetate - Cicek, Demet; Kandi, Basak; Oguz, Sevilay; Cobanoglu, Bengu; Bulut, Serpil; Saral, Yunus (Taylor & Francis Ltd, 2008)
Urticarial vasculitis (UV) is a disease characterized clinically by urticarial skin lesions and histologically by leukocytoclastic vasculitis caused by immunocomplex accumulation in post-capillary venules. Cases induced by various drugs such as cimetidine, diltiazem, potassium iodide, fluoxetine, and non-steroid inflammatory drugs have been reported in the literature. A 48-year-old female who developed pruritus and rash on her body 3 months after starting glatiramer acetate (GA) treatment for multiple sclerosis was diagnosed with UV after clinical and histopathological examination. This report presents the first case in the literature of UV induced by GA.
Keywords: drug eruption; glatiramer acetate; urticarial vasculitis